NILAI PENDIDIKAN AGAMA ISLAM DALAM KARYA SASTRA MODERN - Miftakhul Muthoharoh (Universitas Islam Lamongan, 2019)
Literature is a work that describes the problems of life. Literature in describing human life is inseparable from human and humanitarian problems. The problems in human life are inseparable from the lives of its author and readers, so literature is an effective means of translating the inner world of human beings. Literary works are basically the embodiment of the lives of writers' observations of their surrounding lives. Aside from being entertainment, literary works are also a means conveying the ideas and thoughts in terms of culture, social, and even religion. In literature there are constituent elements, namely themes, mandates, figures, characrers, and languages which are all packaged in aesthetic and imaginative forms. These elements contain ideas related to, among others, religious values. Religious values that are able to color the author's creativity, aesthetics, and imagination include the values of faith, scientific, moral, and social values. These values are the basic ones that form the main foothold in the world of Islamic religious education. This proves that literary works can be a means of transforming written and implied values of life in addition to contributing to the readers and the connoisseurs of literature.